Compositional analysis of excavated landfill samples and the determination of residual biogas potential of the organic fraction - Garcia, J.; Davies, Stewart; Villa, Raffaella; Gomes, Diogo M.; Coulon, Frederic; Wagland, Stuart T. (Elsevier, 2016)
The objectives of this study were to assess the biogas potential of landfilled materials and to further validate the suitability of the enzymatic hydrolysis test EHT as a valuable alternative to substitute the standardised test currently in use (BMP). Both tests were applied to a range of landfill waste samples. The waste composition and volatile solids content (VS) profile together with the BMP test results showed that the biogas potential of the waste samples was directly related to their VS content, as expected. The positive correlation between the VS and the BMP test (r = 0.67) suggests that the first could be used as a primary indicator of biogas potential of waste samples. Nevertheless, it should be validated against the BMP test because, occasionally, the VS content does not equate to the biogas production. This was mainly due to the paper content of the samples which also correlates positively (r = 0.77) with the BMP biogas production. The EHT results showed a higher correlation with the BMP test (r = 0.91) than in previous studies which used a wider mixture of enzymes containing cellulase, hemicellulase and carbohydrase. This finding positions the EHT as a quick assessing method for the biodegradability of waste samples in future sample regimes.
Keywords: Biochemical methane potential; Enzymatic hydrolysis test; Landfill; Biodegradation; Landfill mining